A Review of Range Extender Technologies in Electric Vehicles - Evelyn, Evelyn; Aziz, Abd. Rashid; Sambegoro, Poetro (Unijourn Publisher, 2020)
With the increasing global concern on negative environmental effect from the transportation sector, conventional automobile technologies will not be viable for much longer. Countries like the EU and China have introduced emission related regulations which are stricter than ever. This has compelled automotive manufacturer to turn to Electric Vehicles (EV) as the most effective solution to this issue. There are mainly two types of EV, namely Battery Electric Vehicle (BEV) and Hybrid Electric Vehicle (HEV). Both has its own strength and shortcomings, BEV with zero emission but limited range while HEV has better range at the expense of higher emission. Extended Range Electric Vehicle (EREV) provides a midpoint between these options. This option provides the best of both worlds by allowing users to switch between both systems depending on the vehicle’s operating condition. This paper aims to presents a variety of Range Extender (RE) configurations based on its working principle and type of fuel used. Internal combustion engine, fuel cell, and microturbine are what RE is commonly powered by. The advantages and disadvantages are evaluated and compared to determine the optimal option. It was concluded that depending on fuel availability, space, and efficiency requirement, each configuration has its own merit.